Genetic diversity of two native grassland species from Patagonia: implications for domestication and germplasm conservation - Ignazi, Griselda (2026)
The Patagonian steppe grasslands play a central role in livestock production but are increasingly affected by overgrazing and climate change. To contribute to restoration activities, in this study we evaluated the genetic diversity and population structure of two native grasses across central Patagonia using Sequence-Related Amplified Polymorphism (SRAP) markers. The species Bromus setifolius var. pictus and Poa ligularis var. ligularis present different reproductive strategies, being self-pollinating and cross-pollinating, respectively. Nine populations of each species were analyzed with five primer combinations, producing 87 polymorphic bands in B. setifolius and 95 in P. ligularis. At the species level, P. ligularis showed higher genetic diversity values than B. setifolius, which may be associated with their contrasting reproductive systems. A Bayesian analysis did not reveal clear regional clusters but indicated greater genetic homogeneity in P. ligularis. Gene flow may be promoting genetic mixing among populations, whereas the higher differentiation observed in B. setifolius would result from self-pollination reducing variability and enhancing regional structuring. Analysis of molecular variance indicated that most variation was distributed within populations. Significant genetic differences between populations were observed in both species, with higher differentiation in B. setifolius, including a higher number of private bands in western populations, consistent with in situ persistence in glacial refugia. SRAP markers used for the first time in these species were effective in detecting polymorphism and genetic structure and also allowed us to identify the influence of reproductive systems and historical processes, providing a basis for germplasm conservation and breeding programs to restore degraded Patagonian grasslands under increasing aridity.